The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1998
DOI: 10.1002/pro.5560070228
|View full text |Cite
|
Sign up to set email alerts
|

Stability and folding properties of a model β‐sheet protein, Escherichia coli CspA

Abstract: Although P-sheets represent a sizable fraction of the secondary structure found in proteins, the forces guiding the formation of P-sheets are still not well understood. Here we examine the folding of a small, all P-sheet protein, the E. coli major cold shock protein CspA, using both equilibrium and kinetic methods. The equilibrium denaturation of CspA is reversible and displays a single transition between folded and unfolded states. The kinetic traces of the unfolding and refolding of CspA studied by stopped-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(46 citation statements)
references
References 54 publications
3
43
0
Order By: Relevance
“…However, the positive peak at 230 nm, originating from the aromatic contribution to the far-UV CD spectrum~Woody, 1994; Krittanai & Johnson, 1997! as well as the negative peak above 200 nm, is consistent with the spectra exhibited by several small structurally characterized b-sheet structures, suggesting that the WW domain is folded under these conditions~the N-and C-termini are disordered in the folded structure, partially explaining the random coil-like CD spectrum!~Viguera et al, 1994; Knapp et al, 1998;Reid et al, 1998!. The thermal unfolding profile of the WW domain was monitored at 202 and 230 nm in the temperature range from 4 to 88 8C, both during the course of heat-induced unfolding and cooling-induced refolding. At 202 nm no significant changes in the magnitude of the CD signal were observed up to approximately 80 8C, but a slight loss in signal was noticed at 88 8C~Fig.…”
Section: Thermal Unfolding and Reconstitution Of Wwsupporting
confidence: 78%
“…However, the positive peak at 230 nm, originating from the aromatic contribution to the far-UV CD spectrum~Woody, 1994; Krittanai & Johnson, 1997! as well as the negative peak above 200 nm, is consistent with the spectra exhibited by several small structurally characterized b-sheet structures, suggesting that the WW domain is folded under these conditions~the N-and C-termini are disordered in the folded structure, partially explaining the random coil-like CD spectrum!~Viguera et al, 1994; Knapp et al, 1998;Reid et al, 1998!. The thermal unfolding profile of the WW domain was monitored at 202 and 230 nm in the temperature range from 4 to 88 8C, both during the course of heat-induced unfolding and cooling-induced refolding. At 202 nm no significant changes in the magnitude of the CD signal were observed up to approximately 80 8C, but a slight loss in signal was noticed at 88 8C~Fig.…”
Section: Thermal Unfolding and Reconstitution Of Wwsupporting
confidence: 78%
“…24 The mutation study of F20 and F31 for Csp from E. coli 13 suggested that these two residues should be present in the TS, that is, b2 and b3 might folded. This argument is also supported by the studies of Reid et al 12 that the presence of an oligonucleotide can increase the folding rate as such an oligonucleotide can bind the hydrophobic residues located in b2 and b3. Perl et al 9 have proposed that the N-terminal region is folded but the C-terminal is not in the TS.…”
Section: The Folding Mechanism Of Cspmentioning
confidence: 58%
“…Meanwhile, Csps have been known as a protein family that can fold fast in a two-state folding mechanism 3 as Schmid and coworkers showed that the folding dynamics of CspB from B. subtilis follows a two-state model in 1995. 4 Folding of Csps from several organisms, for example, B. subtilis, 3-8 B. caldolytics, 3,9-11 , Escherichia coli, [12][13][14][15][16] and Thermotoga maritima, 3 have been studied intensively by ensemble experiments. With the advances in single-molecule techniques, valuable insights have been gained from recent single molecule fluorescence energy transfer (FRET) studies of the Csp from T. maritima.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations